Output feedback control of a skid-steered mobile robot based on the super-twisting algorithm. (January 2017) - Salgado, I.; Cruz-Ortiz, D.; Camacho, O.; Chairez, I.
Abstract: This paper presents the design and implementation of an output feedback controller based on the super twisting algorithm (STA) that stabilizes the trajectory tracking error of a skid steered mobile robot (SSMR). The control scheme introduces a diffeomorphism based on the mathematical model of the SSMR to transform the original problem into a third order chain of integrators. In this study, the available measurements are the position and orientation of the SSMR. A modified STA working as a step by step differentiator estimates the velocity and acceleration of the mobile robot. Then, a second STA enforces the tracking of a predefined trajectory. Numerical and experimental results comparing the STA with a state feedback controller (SFC) and a first order sliding mode controller (FOSM) justify the control proposal. Abstract : Highlights: Super twisting algorithm (STA) stabilizes the trajectory tracking error of a skid steered mobile robot. There is a diffeomorphism to transform the SSMR model into a third order chain of integrators. A modified step by step differentiator estimates velocity and acceleration of the mobile robot. A different STA working as controller yields the trajectory tracking error to the origin. Numerical and experimental results justified the control proposal based on STA.